The sniffles for Bear - Becker, Bonny; Denton, Kady MacDonald (Somerville, Mass. : Candlewick Press, 2011)
Certain that no one has even been as sick as he is, Bear resists Mouse's efforts to cheer him and cure his cold.
Keywords: Cold (Disease) -- Juvenile fiction; Sick -- Juvenile fiction; Bears -- Juvenile fiction; Mice -- Juvenile fiction; Friendship -- Juvenile fiction; Picture books for children; Cold (Disease) -- Fiction; Sick -- Fiction; Bears -- Fiction; Mice -- Fiction; Friendship -- Fiction; Cold (Disease) -- Fiction; Sick -- Fiction; Bears -- Fiction; Mice -- Fiction; Friendship -- Fiction